A novel candidate cis-regulatory motif pair in the promoters of germline and oogenesis genes in C. elegans - Linhart, Chaim; Halperin, Yonit; Darom, Amir; Kidron, Shahar; Broday, Limor; Shamir, Ron (Genome Research, 2012)
In this study we report on a novel pair of cis-regulatory motifs in promoter sequences of the nematode Caenorhabditis elegans. The motif pair exhibits extraordinary genomic traits: The order and the orientation of the two motifs are highly specific, and the distance between them is almost always one of two frequent distances. In contrast, the sequence between the motifs is variable across occurrences. Thus, the motif pair constitutes a nearly combinatorial sequence configuration. We further show that this module is conserved among, and unique to, the entire Caenorhabditis genus. By analyzing several gene expression data sets, our data suggest that this motif pair may function in germline development, oogenesis, and early embryogenesis. Finally, we verify that the motifs are indeed functional cis-regulatory elements using reporter constructs in transgenic C. elegans.